Transnational Perspectives on Character Education in Islamic Schools: A Comparative Study of Indonesia and Thailand - Nuruzzaman, Muhammad Adib; Sholihah, Nikmatus; Nisa, Mas Ayu Ainun; Zaini, Achmad; Naf'an, Abdul Wahab (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Character education is designed to counteract the low moral ethics and weak character of students. In its implementation, continuous improvement and development are necessary. This study aims to compare the enhancement of character education in Islamic schools in Indonesia, with the sample of MI Muhammadiyah 5 Surabaya and in Thailand, with the sample of Phatnawitya School Yala. These two schools represent different yet complementary approaches in integrating character values into their respective education systems. This study adopts a qualitative method with a multi-case study design. The data is analysed with in-depth individual case analysis to understand the specific context of each school. Then, a constant comparative method is carried out to compare the results of each case to find the main patterns, differences, and themes. This study uses Bronfenbrenner's Ecological Systems Theory as a theoretical framework, which views the development of individuals as influenced by the interaction between individuals and the various layers of the social environment that exist around them. The results of the study show that strengthening character education not only emphasizes cognitive aspects, but also integrates affective and psychomotor aspects harmoniously. At MI Muhammadiyah 5, character education focuses on Islamic values through habituation, character-based learning, and teacher role example. Meanwhile, Phatnawitya School Yala emphasises a religious attitude, empathy, and discipline in Islamic lessons, academic lessons, and the development of students' specialist skills. Despite being in different educational contexts, both schools managed to develop character education models that were relevant to their respective cultures and systems.